Neurohypophysial Receptor Gene Expression by Thymic T Cell Subsets and Thymic T Cell Lymphoma Cell Lines - Hansenne, I. (Hindawi Publishing Corporation, 2004)
Abstract Neurohypophysial oxytocin (OT) and vasopressin (VP) genes are transcribed in thymic epithelium, while immature T lymphocytes express functional neurohypophysial receptors. Neurohypophysial receptors belong to the G protein-linked seven-transmembrane receptor superfamily and are encoded by four distinct genes, OTR, V1R, V2R and V3R. The objective of this study was to identify the nature of neurohypophysial receptor in thymic T cell subsets purified by immunomagnetic selection, as well as in murine thymic lymphoma cell lines RL12-NP and BW5147. OTR is transcribed in all thymic T cell subsets and T cell lines, while V3R transcription is restricted to CD4(+) CD8(+) and CD8(+) thymic cells. Neither V1R nor V2R transcripts are detected in any kind of T cells. The OTR protein was identified by immunocytochemistry on thymocytes freshly isolated from C57BL/6 mice. In murine fetal thymic organ cultures, a specific OTR antagonist does not modify the percentage of T cell subsets, but increases late T cell apoptosis further evidencing the involvement of OT/OTR signaling in the control of T cell proliferation and survival. According to these data, OTR and V3R are differentially expressed during T cell ontogeny. Moreover, the restriction of OTR transcription to T cell lines derived from thymic lymphomas may be important in the context of T cell leukemia pathogenesis and treatment.